Work Autonomous and Controlled Motivation on Chinese Employees' Work Performance and Innovative Work Behaviour: The Moderating Role of Financial Stress - Ren, Feifei; Zhang, Qian; Wei, Xing (Frontiers in Psychology, 2021)
This study applied self-determination theory (SDT) to investigate the relationships between work motivation and Chinese employees’ work behavior and the moderating role of financial stress. Data were obtained from 245 employees of five organizations in China using a convenience sampling technique. The results indicated that autonomous motivation positively predicted work performance and innovative work behavior while controlled motivation had a positive effect only on employees’ work performance. In addition, financial stress moderated the relationships between autonomous motivation and employees’ work performance and innovative work behavior. Specifically, the beneficial effect of autonomous motivation on work performance and innovative work behavior disappeared when financial stress was high. The findings of the present study supported cultural similarities in the positive role of autonomous motivation and showed cultural differences in the role of controlled motivation. The implications of this study are also discussed.